International Bar Association - Terashima, Yoshimatsu. author. aut Link
II, 44 p.
Keywords: ation" and "Conciliation Terms," with further supplementary notes on "Methods of Conciliation of Domestic Matters." Inasmuch as the practice of domestic matters conciliation is a most important job, it is very difficult to describe it adequately. Feeling a great responsibility imposed upon my shoulder, I have to confess that I prepared this little pointer with great toil and application. I am afraid, however, that due to my mediocrity and immaturity I may have committed some inadvertent errors or dogmatic assertions. I am glad to say that after having shown this paper to my seniors I have obtained their approval on its publication. Just full three years have elapsed since I engaged myself in the conciliation of domestic matters. But that holy mysterious land of treasure lies still unconquered beyond many rivers and, mountains far in the distance. So we pilgrims must devote ourselves heart and soul to the steady progress of study. If this small work proves a mile stone towards our destination, I shall be happier than I expected. Relying on good walkers in our party, I sincerely pray that they will before long reach the summit of the sacred mountain where they can command a grand view of the vast field of legislation. (Jan. 1951) CHAPTER 1. INTRODUCTION 2. A men d men t tot h e C i viI Cod e and D 0 m est i c ReI a t ion s Law and the F ami 1 y C 0 u r t.